Analisis Peningkatan Daya Tarik Wisatawan Pemandian Air Panas Lintang Waterpark Tempuran - Ahmad Bayu; Purwanto Purwanto; Achmad Nur Alfianto (Jurnal Mirai Management, 2023)
This study aims to determine the efforts made by managers in developing the Lintang Waterpark Tempuran Hot Spring Tourism Object to increase the number of tourist visits. This study used descriptive qualitative method. The subjects of this study are managers, employees and the surrounding community who will later provide data on tourism development. While the object of this research is the promotion, management, strengths and weaknesses of the Lintang Waterpark Tempuran Hot Spring Tourism Object affecting the economic progress of the people in the area because it opens up job opportunities for the surrounding community starting from employees, traders, to the land used for parking. Of course this is very helpful for the community in improving the family economy. With relatively cheap prices and easily accessible locations, it affects the number of tourist visits. The Lintang Waterpark Tempuran Hot Springs Tourism Object has strengths and weaknesses, namely the strengths of the Tempuran Lintang Hot Springs Tourism Object include the pool design which is suitable for all ages ranging from children, adolescents, to adults. Meanwhile, the weakness of the Lintang Waterpark Tempuran Hot Spring Tourism Object is the access road to the location is damaged. Keywords : Management, Hot Springs, Maqasid Syariah, SWOT Analysis